Replacement of the proximal humerus with MUTARS tumor endoprostheses - Raiss, Patric; Kinkel, Stefan; Sauter, U.; Bruckner, Thomas; Lehner, Burkhard (European journal of surgical oncology, 2010)
Background and objectives - The aim of this study was to analyze our results using a modular endoprosthetic replacement system (MUTARS) for bone tumors of the proximal humerus. - Methods - Thirty-nine patients were treated with a MUTARS endoprosthesis of the proximal humerus. Mean follow-up duration was 38 months (3-138 months). Most operations were necessitated by metastasis (n=30); surgery for a primary tumor (n=9) was less frequent. The Enneking score was recorded and the active ranges of motion for shoulder flexion, abduction, and external rotation. Complete refixation of the rotator cuff was possible in 23 cases. Radiographs of the affected shoulders were obtained in two planes. - Results - Patient survival was 77% at 2 years and 45% at 11.5 years after surgery. The survival rate of the limb was 90% at 11.5 years. The mean Enneking score was 19 points (range 7-27 points). The mean shoulder flexion was 34° (range 0-90°), abduction 33° (range 0-90°), and external rotation 12° (range 10-50°). Patients with a complete rotator cuff repair showed a significant better range of motion compared to patients with a partial or no repair (p<0.015). No signs of implant loosening were observed on postoperative radiographs. Seven complications occurred, five of them leading to implant revision. At 11.5 years after surgery, the survival rate for the whole cohort without complications was 72%, without revision of the implant 70%. - Conclusions - Replacement of the proximal humerus with MUTARS endoprosthesis is a viable treatment option for bone tumors with satisfying results.